Agricultural land dispute and difficult mediation of religious institutions in the irrigated perimeter of Lagdo (North Cameroon) - MFEWOU, Abdoulay (IJRDO - Journal of Social Science and Humanities Research, 2018)
This research finding carries out a mediation analysis in relation to the different religious institutions in the agricultural land conflict opposing the migrant peasants and the agro-industrial society of Benoue (SAIB) in the irrigated perimeter of Lagdo. This conflict awakes some other dormant conflicts among the actors. That conflict permits us to identify the main generator factors of conflict in Northern part of Cameroon. Among others, the installation of the migrants along the project corridors without any land guarantee, the lack of recognition of the individual right on the land, the antagonism of traditional power and the state power in the land issue, the agricultural land system to the peasant within the irrigated perimeter and the modalities of land heritage. This very conflict was put to the knowledge of the traditional rulers, the public administration till the Presidency of the Republic and return to the lamidat (traditional chief) and has given birth to mediation attempt by the religious institutions (Muslim, catholic, protestant, animist) whom only the Diocesan Committee (catholic) has highlighted the peasant will, but was limited. That is because those land conflicts has taken a political brake and engage the state ahead of its responsibilities to apply the legislative law or to revise the said law which will ensure land security in the Northern part of the Country through facilitation and effective decentralization.